The Effect of Warm Compression Applied before Heel Lance on Pain Level, Comfort Level and Procedure Time in Healthy Term Newborns: A Randomized Clinical Trial - Özlem KarabıyıkOğurlu; Esra TuralBüyük; Osman Yildizlar (Mashhad University of Medical Sciences, 2020)
Background & aim: Warm compression is an effective method preferred in relieving pain. It enables procedures to be completed in a shorter time, and with less pain due to increasing blood flow in the area. This study aimed to investigate the effects of warm compress applied before heel lance on the procedure time, level of pain, and comfort level of healthy term newborns. Methods: This randomized controlled clinical was conducted on 80 neonates who were randomly divided into experimental and control groups.  The data were collected using demographic questionnaire, observation checklist for procedure, Neonatal Infant Pain Scale (NIPS), and The Comfort Behaviour Scale (TCBS). The experimental group was subjected to local dry mild-warm compression to the heel before the heel lance procedure. The control group received routine heel lance procedure. Body temperature, peak heart rate, and oxygen saturation levels before, during, and after the procedure were recorded in both groups. Data were analyzed in SPSS software (version 16) using the Chi-square test and Mann-Whitney U test. Results: The results of the study showed shorter procedure time in the experimental group compared to the control group (P<0.05). Moreover, the mean NIPS and TCBS total scores were lower in the experimental group compared to control group, and this was found to be statistically significant (P<0.05). Conclusion: It was found that warm compression applied before heel lance decrease the length of the procedure and is effective in decreasing pain and providing comfort in newborns.